Adjuvant music therapy for patients with hypertension: a meta-analysis and systematic review - Min Cao; Zhiyuan Zhang (BMC, 2023)
Abstract Background High blood pressure, anxiety, depression and sleep disorder is very common in patients with hypertension. We aimed to perform a meta-analysis to evaluate the effects of adjuvant music therapy for patients with hypertension, to provide insights to the clinical management of hypertension. Methods Two authors searched PubMed, Embase, Web of Science, the Cochrane Library, Chinese National Knowledge Infrastructure, China Biomedical Literature Database, Wanfang Databases for randomized controlled trials (RCTs) on the role of music therapy in hypertension up to Oct 15, 2022. RevMan 5.3 software was used for meta-analysis. Results A total of 20 RCTs including 2306 patients were finally included. 1154 patients received music therapy. Meta-analysis showed that music therapy can effectively reduce the systolic blood pressure(MD = − 9.00, 95%CI: − 11.99~- 6.00), diastolic blood pressure(MD = -6.53, 95%CI: -9.12~- 3.93), heart rate (MD = -3.76, 95%CI: -7.32~- 0.20), self-rating anxiety scale (SAS) score(MD =-8.55, 95%CI: -12.04~-4.12), self-rating depression scale (SDS) score(MD = -9.17, 95%CI: -13.85~-5.18), Hamilton anxiety scale (HAMA), score(MD = -3.37, 95%CI: − 5.38~- 1.36), PSQI score(MD =-1.61, 95%CI:-2.30~- 0.93) compared with routine therapy in patients with hypertension(all P < 0.05). No publication bias in the synthesized outcomes were found (all P > 0.05). Conclusion Music therapy can effectively control blood pressure and heart rate, reduce anxiety and depression levels, and improve sleep quality in hypertensive patients. Limited by the quantity and quality of included studies, the above conclusions need to be verified by more high-quality studies.